Energy performance evaluation of a photovoltaic thermal phase change material (PVT-PCM) using a spiral flow configuration - Muhammad Syazwan Bin Aziz; Adnan Ibrahim; Muhammad Amir Aziat Bin Ishak (International Journal of Renewable Energy Development, 2023)
A relatively new technology, a hybrid photovoltaic thermal (PVT) solar collector, allows for producing electrical and thermal energy.  However, the module heats up more when exposed to sunlight thanks to the PVT collector's incorporation, reducing its efficiency.  Consequently, lowering the operating temperature is crucial for maximizing the system's effectiveness.  This research aims to create a photovoltaic thermal phase change material (PVT-PCM) solar collector and evaluate its energy performance through a controlled laboratory environment.  Two different PVT collector designs, one using water and the other using a phase change material (PCM), were evaluated using a spiral flow configuration.  Under a sun simulator, the PVT solar collector was subjected to 400 W/m2, 600 W/m2, and 800 W/m2 of solar irradiation at three different mass flow rates.  The results showed that under 800 W/m2 of solar irradiation and 0.033 kg/s mass flow rate, the collector using water could only reach an overall maximum efficiency of 64.34 %, whereas the PVT-PCM configuration with spiral flow had the maximum performance, with an overall efficiency of 67.63%.